Knowledge on Self-care Management among Chronic Kidney Disease Patients Undergoing Hemodialysis in Tertiary Hospitals of Kathmandu - Dev, Renu; Sah, Bimala K; Onta, Mandira (Journal of Institute of Medicine Nepal, 2021)
Introduction: Chronic kidney disease (CKD) is an alarming public health problem worldwide which often needs maintenance hemodialysis. Self-care management involves the positive efforts of patients to participate in their health care in order to optimize health. Thus this study aims to assess the knowledge on self-care management among chronic kidney disease patients undergoing hemodialysis. Methods: A descriptive cross-sectional study was carried out at Tertiary hospitals, Kathmandu among 173 hemodialysis patients using purposive sampling technique. Data was collected through face to face interview from June to July, 2018. Self-care management constituted four components: diet and fluid intake, physical activities and exercises, care of fistula and other general management of hemodialysis. Data was analyzed with SPSS version 20 by using descriptive statistics and inferential statistics. Results: The mean age of respondents was 45.71±14.61 years. Seventy (40.5%) were on hemodialysis for less than one year and majority (79.8%) underwent hemodialysis twice a week. The overall mean score of knowledge was 60.26±8.90. The mean score of knowledge on diet and fluid intake, physical activities and exercises, care of fistula and other general management of hemodialysis were 62.41±7.70, 47.27±20.59, 68.08±12.43 and 42.69±17.33 respectively. There were significant association between level of knowledge score and educational status and attending educational programme on hemodialysis (p=0.001 and p=0.01). Conclusion: Only few respondents had good level of knowledge on self-care management. Thus, it is immensely needed to conduct regular educational programme focused on diet and fluid, physical activities and exercise, fistula care and general management of stress and complications.